Older Adults’ Engagement with Further and Higher Education in the West of Scotland: Tracking Educational Journeys - Brian Findsen; Sarah McCullough (Adult Education Research Conference, 2007)
In this qualitative study, the motivations and trigger events for learning of West of Scotland older adults are explored. The range of purposes for formal learning in later adulthood is broader than most conventional typologies would suggest and work-related motives are shown to be very strong, linked to on-going vocational aspirations.